PROGRAM PENDAMPINGAN PEMBELAJARAN DALAM MENGEMBANGKAN KREATIVITAS DAN PENGALAMAN BELAJAR SISWA DI SD NEGERI PABUARAN 04 - Sintia Rahmah; Ahmad Rifa’i; Annisa Annisa; Aliyah Sofiyani; Agnes Oktavia Saragih; Ayang Fristia Maulana; Rani Sri Sumarsih (Yayasan Education and Social Center, 2026)
The learning assistance program is a form of community service aimed at improving the quality of learning while fostering students' creativity and meaningful learning experiences in elementary schools. This program was implemented at SD Negeri Pabuaran 04, Serang Regency, Indonesia, involving fifth-grade students in learning assistance and ecoprint activities, as well as fourth-, fifth-, and sixth-grade students in an anti-bullying awareness program. The program employed a structured learning assistance approach through interactive lectures, demonstrations, discussions, question-and-answer sessions, hands-on practice, and the implementation of Problem-Based Learning (PBL), Project-Based Learning (PjBL), and Teams Games Tournament (TGT) learning models. The activities included learning assistance in Physical Education, Natural and Social Sciences, Pancasila Education, Mathematics, ecoprint practice, and anti-bullying socialization. The results showed that students actively participated and demonstrated high enthusiasm throughout the activities. The application of innovative learning models successfully enhanced students' learning motivation, creativity, critical thinking skills, collaboration skills, and meaningful learning experiences. Furthermore, the anti-bullying program strengthened students' character by increasing their awareness of the importance of creating a safe, comfortable, and respectful school environment. Overall, the collaboration between Universitas Bina Bangsa students through the Community Service Program (Kuliah Kerja Mahasiswa KKM) and the school made a positive contribution to improving the quality of classroom learning and supporting the holistic development of elementary school students.